KAJIAN MODAL SOSIAL DALAM KELOMPOK TANI DI DESA TOMBOLANGO KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA (STUDI KASUS KELOMPOK TANI KEONG MAS DAN KELOMPOK TANI PANGAN JAYA) - Korompot, Silvia; Talumingan, Celcius; Rengkung, Leonardus Ricky (Sam Ratulangi University, 2022)
This study aims to determine how social capital is in the Keong Mas farmer group and Pangan Jaya farmer group in Kunciango Village, Sangkub District, North Bolaang Mongondow Regency. The research was conducted from November 2021 to January 2022. The data used in this study were primary data and secondary data. Primary data were obtained through direct interviews with 25 respondents from members of the Keong Mas farmer group with 13 respondents and Pangan Jaya farmer group with 12 respondents using a questionnaire and secondary data obtained from the village government office in Kunciango. The sampling method was carried out intentionally (purposive sampling). The data analysis method used is descriptive qualitative. The results showed that the elements of social capital, namely trust, network and norms, the two groups were very different in that the Keong Mas farmer group had very good social capital. So as to increase the existence and cohesiveness of group members. On the other hand, in the Pangan Jaya farmer group, the elements of social capital are rarely even reduced, so to increase their existence and cohesiveness, the Pangan Jaya farmer group needs to increase social capital such as the Keong Mas farmer group so that it will be better in the future.